Detection and discrimination of biofilm populations using locked nucleic acid/2'-O-methyl-RNA fluorescence in situ hybridization (LNA/2'OMe-FISH) - Azevedo, Andreia (2015)
Multispecies biofilms are the dominant form of biofilms found in Nature. The application of fluorescence in situ hybridization (FISH)-based techniques to the discrimination of biofilm populations might contribute to the understanding of microorganism interactions in these structures, and might allow the development of efficient strategies to prevent or minimize biofilm-associated diseases. This work presents the first study that develops, optimizes and validates a multiplex FISH procedure using locked nucleic acid (LNA) and 2-O-methyl RNA (2OMe) oligonucleotides probes for the in vitro discrimination within mixed populations. As a case study, Escherichia coli, the major cause of urinary tract infections (UTIs), and three other atypical colonizers of urinary catheters (Delftia tsuruhatensis, Achromobacter xylosoxidans and Burkholderia fungorum) with unproven pathogenic potential, were selected. Specific probes for these species were designed and optimized for specific hybridization in multiplex experiments. Results showed that the LNA/2OMe-FISH method performed well in multiplex experiments and presented a good correlation with total and cultivability counts, regardless of the cells physiological state. In fact, the method was also able to report variations of viable but non-cultivable populations. Further analysis of mixed biofilm structures by confocal laser scanning microscopy provided a clear discrimination in three dimensions between the location of the different populations.